Outline of the Problem of Sexual Violence against Children Including STD - Katarzyna Plagens-Rotman; Grażyna Jarząbek-Bielecka; Dorota Lorkiewicz-Muszyńska; Agnieszka Przystańska; Anna Obrębowska; Mariola Pawlaczyk; Ewa Jakubek; Mizgier Małgorzata; Magdalena Pisarska-Krawczyk; Michał Pawlaczyk; Justyna Opydo-Szmaczek; Dawid Luwański; et al. (IMR Press, 2023)
Objective: Sexual and reproductive health is an integral part of the health and well-being of adolescents. In this paper, the authors summarized the outline of the problems of sexual violence against children, with special emphasis on that against girls. The commentary was written from the point of view of general gynaecologists, sexologists, obstetrics and gynaecology nurses, clinical psychologist, and dermatologist. Mechanism: For the convenience of the readers' better understanding, we described things in the following order; first, we explained the concept of child sexual abuse, then we discussed symptoms of sexual violence against children, and special attention was given to the issue of Sexually Transmitted Diseases (STD). Lastly, we emphasized general principles of physical diagnostics in the case of suspicion of sexual harassment of children. Findings in Brief: This work reveals the importance of holistic care of sexual assault victims. Conclusions: The cooperation of gynaecologists with dermatologists, medical examiners, paediatricians, psychologists, and dieticians is essential to interdisciplinary collaboration for children. Acquaintance by doctors with symptoms that can be a sign of sexual abuse of a child is necessary. If they appear in the form of physical injuries or STDs, they will probably be possible to diagnose only by medical service.